Огляд методів виявлення раку молочної залози з використанням штучного інтелекту і методів поглибленого навчання - Naderan, Maryam (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2021)
Nowadays, there are many related works and methods that use Neural Networks to detect the breast cancer. However, usually they do not take into account the training time and the result of False Negative (FN) while training the model. The main idea of this paper is to compare already existing methods for detecting the breast cancer using Deep Learning Algorithms. Moreover, since the breast cancer is one of the most common lethal cancers and early detection helps prevent complications, we propose a new approach and the use of the convolutional autoencoder. This proposed model has shown high performance with sensitivity, precision, and accuracy of 93,50%, 91,60% and 93% respectively.